Debt and Macro Stability - Marc Jarsulic (Levy Economics Institute of Bard College, 1989)
There has been much recent interest in the problem of financial instability in the macro economy. Some researchers have looked for cyclical and secular co-movements between debt accumulation, financial crises, and problems in the real economy. Others have tried to rationalize, in formal models the apparent connections between finance, changes in expectations, and macro instability. Two different points of view are embodied in this work. One, deriving from the work of Minsky, emphasizes the importance of ignorance and psychology. Firms are seen as financing accumulation on the basis of unverifiable expectations, accumulating debt burdens in the process. When the debt burdens are large enough, the economy becomes vulnerable to downward revisions of expectations. Such revisions reduce effective demand and stimulate financial crises. A second view emphasizes a structural determinant, of instability – declining profitability. Problems with profits are viewed as a major cause of debt burdens, and the source of potential financial crisis. What follows is an attempt to synthesize these two viewpoints in a manageable analytical framework. To set the stage, we begin with a brief review of Minsky's ideas, which have to this point received the greater attention. This is followed by a discussion of the structuralist view and some of the key supporting empirical evidence. Next a Keynes-Kalecki model of growth with debt is constructed. It suggests that in economies where debt finances accumulation, stable and unstable configurations of economic variables coexist simultaneously. The proximity of these regions is shown to depend on expectational and distributional factors. The model therefore introduces a way to characterize financial fragility in terms of stability theory, and shows how structuralist and Minskian ideas complement each other.
Keywords: 330